Application of the POD method to nonlinear dynamic analysis of reinforced concrete frame structures subjected to earthquakes. (1st November 2022) - Ayoub, Naim; Deü, Jean-François; Larbi, Walid; Pais, Joseph; Rouleau, Lucie
Highlights: Extension of the POD to nonlinear dynamic analysis of reinforced concrete structures. First time application of POD to reinforced concrete with material nonlinearities. Computational cost of nonlinear dynamic analysis is reduced by up to 94 % POD modes less dependent on initial loading. Abstract: For the purpose of reducing computational cost, this paper presents an extension of the Proper Orthogonal Decomposition method (POD) to nonlinear dynamic analysis of reinforced concrete multistory frame structure. The material nonlinearity, due to plasticity and damaging, is modeled by the multifiber section approach. An initial expensive full model nonlinear time-history analysis is conducted for the frame structure subjected to a portion of an initial seismic base excitation. Then, POD modes are extracted and used to reduce the dynamic model for the rest of the initial base excitation or for multiple different ones. By comparing the full and reduced models, the computational cost was lowered by up to 94 % while maintaining good level of accuracy.